2008
DOI: 10.1681/asn.2007060709
|View full text |Cite
|
Sign up to set email alerts
|

CLDN16 Genotype Predicts Renal Decline in Familial Hypomagnesemia with Hypercalciuria and Nephrocalcinosis

Abstract: Familial hypomagnesemia with hypercalciuria and nephrocalcinosis (FHHNC) is a rare autosomal recessive tubular disorder caused by CLDN16 mutations. CLDN16 encodes the renal tight junction protein claudin-16, which is important for the paracellular reabsorption of calcium and magnesium in the thick ascending limb of Henle's loop. That FHHNC is frequently associated with progressive renal failure suggests additional roles for claudin-16 in the maintenance of tight junction integrity. An investigation of 32 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 43 publications
4
130
0
1
Order By: Relevance
“…First, although FHHNC is mostly diagnosed during the first years of life (age of diagnosis within the first decade for all patients, within the first year of life for 8 of 12 patients) (5), it can be asymptomatic until the end of the second decade as exemplified by patient F2.3. In patients with CLDN16-related FHHNC, a genotype-phenotype correlation has been established and age at onset and severity may be predicted from the CLDN16 genotype (12). Because of the recent recognition of CLDN19 mutations in humans and their low frequency, this analysis has not yet been performed in patients with CLDN19 mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although FHHNC is mostly diagnosed during the first years of life (age of diagnosis within the first decade for all patients, within the first year of life for 8 of 12 patients) (5), it can be asymptomatic until the end of the second decade as exemplified by patient F2.3. In patients with CLDN16-related FHHNC, a genotype-phenotype correlation has been established and age at onset and severity may be predicted from the CLDN16 genotype (12). Because of the recent recognition of CLDN19 mutations in humans and their low frequency, this analysis has not yet been performed in patients with CLDN19 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…FHHNC may be disclosed by a wide variety of symptoms, including recurrent urinary tract infection, polyuria and/or polydipsia, nephrolithiasis, or tetanic convulsions (11). In patients with CLDN16 mutations, progression to ESRD may be predicted by the genotype (12). Of note, Konrad et al emphasized the severe ocular involvement (macular colobomata, nystagmus, myopia, visual loss) shown in CLDN19 contrasting with the mild ocular involvement in some CLDN16 patients (myopia, astygmatism, hypermetropia, strabism) (5,10).…”
Section: Introductionmentioning
confidence: 99%
“…At least 30 different claudin-16 mutations have now been reported in families with FHHNC (13, 56, 60, 65, 66, 76 -78, 88, 91, 94, 95, 100, 110, 111). Several are predicted to prematurely truncate the protein, and many have been shown to cause defects in trafficking of the protein to the plasma membrane (44,57,60). These findings suggested that claudin-16 might function as a divalent cation-selective paracellular pore and that FHHNC could be due to loss-of-function mutations that would be expected to abolish paracellular P Ca and P Mg in the TALH.…”
Section: Role Of Claudins In Human Diseasesmentioning
confidence: 99%
“…23 Many different FHHNC mutations have been identified in the human CLDN16 gene. 48,49 The expression of CLDN16 is restricted to the thick ascending limb (TAL) of the nephron. 23 We transfected a renal model cell line LLC-PK1 with CLDN16 and found a large increase in Na + permeability (P Na ) accompanied by an only moderately enhanced Mg 2+ permeability (P Mg ).…”
Section: Claudin-16mentioning
confidence: 99%